1981
DOI: 10.1021/bi00519a021
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II)-dependent synthesis of diadenosine 5',5'''-P1,P4-tetraphosphate by Escherichia coli and yeast phenylalanyl-tRNA synthetases

Abstract: A new activity of Escherichia coli and yeast phenylalanyl-tRNA synthetases, the conversion adenosine 5' -triphosphate into diadenosine 5' ,5"' -P(1) ,P(4) -tetraphosphate, is reported. This activity is followed by (31)P NMR and chromatography on poly(ethylenimine)-cellulose. It is revealed by the addition of ZnCl2 to a reaction mixture containing the enzyme, ATP-Mg(2+), L-phenylalanine, and pyrophosphatase It reflects the reaction enzyme-bound phenylalanyl adenylate with ATP instead of PPi and strongly depends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
47
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(53 citation statements)
references
References 35 publications
6
47
0
Order By: Relevance
“…Ap4A and Ap4G transiently increased three-to sevenfold after 1 h and then decreased concomitantly with an 80% decrease in the level of ATP after 2 h in the presence of dinitrophenol. These results do not support the hypothesis that Ap4A is a positive pleiotypic activator that modulates DNA replication, but they are consistent with the hypothesis proposed for procaryotes that ApA and Ap4G are signal nucleotides or alarmones of oxidative stress (B. R. Bochner Diadenosine 5',5" '-P',P4-tetraphosphate (Ap4A) and other adenosine tetraphosphonucleoside (Ap4N) and adenosine triphosphonucleoside (Ap3N) compounds are synthesized as side reaction products by tRNA synthetases from several organisms, including Physarum polycephalum (6,19,36,40,55). Zamecnik and Stephenson (54) have suggested that Ap4A might serve as a regulatory nucleotide that couples protein synthesis and transcription or replication.…”
supporting
confidence: 76%
“…Ap4A and Ap4G transiently increased three-to sevenfold after 1 h and then decreased concomitantly with an 80% decrease in the level of ATP after 2 h in the presence of dinitrophenol. These results do not support the hypothesis that Ap4A is a positive pleiotypic activator that modulates DNA replication, but they are consistent with the hypothesis proposed for procaryotes that ApA and Ap4G are signal nucleotides or alarmones of oxidative stress (B. R. Bochner Diadenosine 5',5" '-P',P4-tetraphosphate (Ap4A) and other adenosine tetraphosphonucleoside (Ap4N) and adenosine triphosphonucleoside (Ap3N) compounds are synthesized as side reaction products by tRNA synthetases from several organisms, including Physarum polycephalum (6,19,36,40,55). Zamecnik and Stephenson (54) have suggested that Ap4A might serve as a regulatory nucleotide that couples protein synthesis and transcription or replication.…”
supporting
confidence: 76%
“…In particular, we have been interested in the role of Zn 2ϩ in strongly augmenting the aminoacyl-tRNA synthetase synthesis of adenyl dinucleoside polyphosphates (17)(18)(19) and the role of the ion in the heat shock response. Most of the class II aminoacyl-tRNA synthetases are stimulated by Zn 2ϩ in Ap n A synthesis, yet many do not have clear zinc-binding motifs.…”
mentioning
confidence: 99%
“…produced in the back reaction of the amino acid activation step of protein synthesis [6] and its biosynthesis can be dramatically stimulated by low concentrations (80 pM) of Zn2+ [7]. The site of its intracellular activity has been shown to be the DNA replicative machinery.…”
mentioning
confidence: 99%